Variacions sobre el tema "Corella i els contemporanis valencians" - Martínez Romero, Tomàs (Caplletra. Revista Internacional de Filologia, 1998)
The author provides data concerning the interrealtion between Corella's work and that of some of hiscontemporaries -precisely Ausiàs March, Joan Moreno and Bernat Fenollar-. He analyses in detail the jovial poem dedicated to Bernat del Bosch - a character here identified as historical, and executed for his homosexuality.